Challenges for working women - Camacho Monge, Daniel (2025)
Frequent references are made to the disadvantaged and subordinate situation women face in the workplace regarding salaries, work hours, status, and opportunities for advancement. In this Issue 184 of the Revista de Ciencias Sociales of the University of Costa Rica, whose central theme is "Challenges of Working Women," we aim to delve deeper into these topics with specific studies on women's work across various occupational fields, historical periods, and geographical locations.